Case Report: Optimum excision with split skin graft closure in the management of penile sebaceous carcinoma - Fam, Xeng Inn; Liu, Chian Yong; Md Pauzi, Suria Hayati; Rizuana, Iqbal Hussain (Frontiers in Oncology, 2023)
Sebaceous carcinoma (SC) is a rare malignant skin neoplasm derived from the meibomian gland of adnexal epithelium, which is frequently confused with basal cell carcinoma (BCC), exhibiting sebaceous differentiation and commonly found in the head and neck regions. We report a case of penile sebaceous carcinoma, an extremely rare anatomical site for SC. A 68-year-old man presented with a 4-month history of painless, non-healing ulcerated nodules over the left side of the penile shaft. Wedge biopsy showed adenocarcinoma with signet ring differentiation. We proceeded with wide local excision (WLE) of the lesion with the inclusion of the indurated skin and 5 mm of normal margin, followed by primary closure of the scrotal defect and split skin grafting of the penile shaft by using a thigh skin donor. The final histopathological examination revealed sebaceous carcinoma with pagetoid spread. The patient achieved recurrence-free survival without any form of adjuvant therapy after 4 years of follow-up.